Activity of Several Purine Metabolic Enzymes in Sera of Pregnant Women - Noor Khalid Zaidan 1 , Wisam Mahmood Mohammed 1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aims to determine the activity of several purine metabolic enzymes in the sera of pregnantwomen. These enzymes show potential as indicators to follow the progress of pregnancy. The samples ofthis study were collected from 75 healthy pregnant women. The age range of the sample study was 17–43years and 25 samples were used as control (non-pregnant women in the normal physiological state). Purinemetabolic enzyme activity was compared among the three groups with each other and with control. Resultsappeared high significantly with p ? 0.05 in group III compared with group I of adenosine deaminase and thecontrol group . Pregnant women showed increase significantly level of 5-nucleotidase (5-NT) and alkalinephosphatase (AlP) enzyme activity, particularly in the groups III of 5-NT and AlP compared with group I of5-NT and AlP, the control group was found to possess equal 5-NT and AlP .